1999
DOI: 10.1021/ie980484w
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Lime for N2O Decomposition under Coal Combustion Conditions

Abstract: To understand the contribution of lime to the abatement of N2O emission from fluidized coal combustor, the catalytic activity of the lime for the decomposition of N2O under coal combustion conditions was studied. Lime was active for the catalytic decomposition of N2O, and its activity was stable in the simulated coal combustion flue gas in the absence of SO2 at 800 °C. The catalytic activity of lime was depressed by the presence of CO2, H2O, and SO2. The affect of the presence of SO2 seemed to be most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…The presence of the adsorption band of nitrate verified the production of calcium nitrate in the previous study. 16 The DRIFTS experiment showed that the main adsorption species of N 2 O on the CaO surface was cis-dimer nitroso. The two N atoms in N 2 O interacted with the coordinately unsaturated lattice oxygen on the CaO surface 19,20 to form the adsorbed N 2 O molecule, as shown in eq 6.…”
Section: Setup and Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the adsorption band of nitrate verified the production of calcium nitrate in the previous study. 16 The DRIFTS experiment showed that the main adsorption species of N 2 O on the CaO surface was cis-dimer nitroso. The two N atoms in N 2 O interacted with the coordinately unsaturated lattice oxygen on the CaO surface 19,20 to form the adsorbed N 2 O molecule, as shown in eq 6.…”
Section: Setup and Gasmentioning
confidence: 99%
“…NH 3 dissociation to NH 2 was the rate-controlling step of NH 3 conversion and occurred through eqs 9 and 10. Thus, the reaction rate of NH 3 can be expressed as eq16 …”
mentioning
confidence: 99%
“…Secondly, while the conversion from HCN to NO increases, that to N 2 O decreases with increasing temperature . The emission of N 2 O is mostly controlled by operating conditions such as the combustion temperature and the choice of sorbent for capturing SO x . In contrast to chemical plants for N 2 O abatement during nitric acid production, the catalytic abatement technology for N 2 O has not been developed yet for fluidized bed combustion.…”
Section: Introductionmentioning
confidence: 99%
“…8 Th e emission of N 2 O is mostly controlled by operating conditions such as the combustion temperature 4 and the choice of sorbent for capturing SO x . 9,10 In contrast to chemical plants for N 2 O abatement during nitric acid production, 11 the catalytic abatement technology for N 2 O has not been developed yet for fl uidized bed combustion. Santiago et al 12 suggested that a promising zeolite catalyst (Fe/ZSM-5) could be installed in the fl uidized bed combustion system operated within 530-830 °C for N 2 O direct decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, CaO was active for the direct decomposition of N 2 O in spite of the presence of oxygen and methane. A serious problem related to the practical applications of CaO in real exhaust gases is the deactivation due to the formation of CaSO 4 in the presence of SO 2 20. On the other hand, in several cases, the presence of SO 2 has a promotional effect on the deNO x activity of silver catalysts under lean‐burn conditions 8, 9…”
Section: Introductionmentioning
confidence: 99%